FINANCIAL PERFORMANCE, CORPORATE GOVERNANCE AND SUKUK RATINGS: EVIDENCE FROM INDONESIA - Yusrialis Yusrialis; M. Iqbal Qard Matareng (Faculty of Economic and Social Science, Universitas Islam Negeri Sultan Syarif Kasim, 2025)
Sukuk ratings are an important indicator for investors in assessing the risk and credibility of issuing companies. This study analyzes the influence of profitability, leverage, liquidity, and good corporate governance (GCG) on corporate sukuk ratings for companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period using a quantitative approach. The analysis method uses panel data regression.This study analyzed 39 company observations with 13 sukuk issuing companies selected through purposive sampling.Data processing was performed using EViews 13 with a random effects approach. Test results indicate that partially, profitability, leverage, and Good Corporate Governance (GCG) have a significant relationship with sukuk ratings, while liquidity does not show a significant effect. However, simultaneous testing results indicate that the combination of all independent variables in the model is unable to significantly explain variations in sukuk ratings. This condition is consistent with the relatively low Adjusted R² value, which reflects the limitations of the research model. This finding indicates that although some variables play a role individually, the sukuk rating process is in practice influenced by various factors other than the research model, including qualitative aspects, issuer characteristics, and macroeconomic conditions. Key words: Sukuk rating; financial performance; corporate governance; signaling theory.